1996
DOI: 10.1149/1.1837227
|View full text |Cite
|
Sign up to set email alerts
|

Density of States Calculations of Small Diameter Single Graphene Sheets

Abstract: The densities of states for the TI-band of single graphene sheets with small diameters were calculated by employing a linear combiriation of atomic orbital approach using as the basis set the carbon p. atomic orbitals together with a modified Huckel approximation wherein the overlap integrals out to the fourth nearest neighbors set were included.These densities of states were used to predict the voltage of lithiated carbon vs. lithium metal, an important characteristic for disordered carbon used as the negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
0
29
1
Order By: Relevance
“…Graphene is suggested to have twice as many low energy lithium sites as graphite due to the host of Li ions in both sides (C 3 Li) [81]. This capacity could be further boosted by the suggested covalent Li 2 sites (C 2 Li) [82] and the low energy edge sites (C 1.5 Li) [83]. Elaborating on this reasoning, the presence of a great number of defects (vacancies, topological defects and impurities besides edge defects) in SPG introduced by the oxidation-reduction process [84][85][86][87][88][89] or doping [90][91][92][93] can serve as additional sites for lithiation, further improving the capacity to surpass the theoretical limit.…”
Section: Lithium Ion Batteries (Libs)mentioning
confidence: 99%
“…Graphene is suggested to have twice as many low energy lithium sites as graphite due to the host of Li ions in both sides (C 3 Li) [81]. This capacity could be further boosted by the suggested covalent Li 2 sites (C 2 Li) [82] and the low energy edge sites (C 1.5 Li) [83]. Elaborating on this reasoning, the presence of a great number of defects (vacancies, topological defects and impurities besides edge defects) in SPG introduced by the oxidation-reduction process [84][85][86][87][88][89] or doping [90][91][92][93] can serve as additional sites for lithiation, further improving the capacity to surpass the theoretical limit.…”
Section: Lithium Ion Batteries (Libs)mentioning
confidence: 99%
“…Carbonaceous materials, such as graphite67, carbon nanofibers89, carbon nanotubes101112 and porous carbon1314, are promising anode materials in LIBs due to their high Li-storage capacity, high conductivity, decent electrochemical activity and low cost1516. In particular, graphene has attracted extensive research interests with a theoretical maximum lithium capacity of 784 mAh/g by forming Li 2 C 6 structure17, and an even higher capacity up to 1488 mAh/g for an isolated graphene flake that is only 0.7 nm in diameter1819. However, it was found that the Li capacity of some graphene samples can be even significantly lower than that of bulk graphite20, possibly due to the formation of small Li clusters on graphene as the interaction between Li atoms212223 is much stronger than that between Li and pristine graphene242526.…”
mentioning
confidence: 99%
“…0.7 nm thickness could provide the highest density storage (with a Li 4 C 6 stoichiometry). [17] Furthermore, modification of the graphite by oxidation (to graphite oxide) results in the formation of nucleophilic sites (carboxyl or hydroxyl groups, for example), which facilitate the interaction with positively charged polyelectrolytes, while the epitaxial adsorption of polymers, such as poly(ethylene oxide) (PEO), occurs preferentially in the unmodified graphitic domains. [18] Finally, nanostructuring provides a molecular level control of the electrode composition, which, in turn, permits a systematic variation of different parameters and the elucidation of the charge storage mechanism.…”
mentioning
confidence: 99%
“…1). A lithium to carbon ratio of 1:2 (compound LiC 2 ) is only achievable with small diameter graphene sheets, [5,17] suggesting that the oxidative treatment leading to GO generated important edge modifications and disruptions of the conjugation length, leading to smaller graphitic domains. Using the self-assembled submicrometer-thick S-(PDDA/GO/ PEO) 10 electrode (Film III) prepared in this work, we have discovered a new route to the nanofabrication of fully reversible Li-ion batteries.…”
mentioning
confidence: 99%